Climate–urban nexus: A study of vulnerable women in urban areas of KwaZulu-Natal province, South Africa - Hlahla, Sithabile; Simatele, Mulala Danny; Hill, Trevor; Mabhaudhi, Tafadzwanashe (Weather, Climate, and Society, 2022)
The changes in climatic conditions and their associated impacts are contributing to a worsening of existing gender inequalities and a heightening of women’s socioeconomic vulnerabilities in South Africa. Using data collected by research methods inspired by the tradition of participatory appraisals, we systematically discuss the impacts of climate change on marginalized women and the ways in which they are actively responding to climate challenges and building their adaptive capacity and resilience in the urban areas of KwaZulu-Natal, South Africa. We argue that changes in climate have both direct and indirect negative impacts on women’s livelihoods and well-being. Less than one-half (37%) of the women reported implementing locally developed coping mechanisms to minimize the impacts of climate-related events, whereas 63% reported lacking any form of formal safety nets to deploy and reduce the impacts of climate-induced shocks and stresses. The lack of proactive and gender-sensitive local climate change policies and strategies creates socioeconomic and political barriers that limit the meaningful participation of women in issues that affect them and marginalize them in the climate change discourses and decision-making processes, thereby hampering their efforts to adapt and reduce existing vulnerabilities. Thus, we advocate for the creation of an enabling environment to develop and adopt progendered, cost-effective, transformative, and sustainable climate change policies and adaptation strategies that are responsive to the needs of vulnerable groups (women) of people in society. This will serve to build their adaptive capacity and resilience to climate variability and climate change–related risks and hazards. © 2022 American Meteorological Society.
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; afrique du sud; approches et analyses; changements climatiques; environnement; histoire et politique; patriarcat; pauvreté; projet charge mentale; périodes historiques; régions géographiques; système colonial; systèmes d'oppressions; thématiques

État de lieu des données internationales sur les inégalités de genre dans le développement international - Machkouri, Zora Ait El; Bourassa-Dansereau, Caterine; Langevin, Marie (Cahiers de recherche OFDIG, 2022)
Ce cahier présente un premier état des lieux du développement inclusif par le genre (DIG) et brosse le portrait des sources de données internationales et institutionnelles existantes et accessibles au sujet du développement inclusif afin d’outiller l’Observatoire et de soutenir ses partenaires dans leur volonté de se saisir de cette problématique de l’égalité et de participer concrètement aux défis qui en découlent. En répertoriant les sources de données existantes, en analysant leurs caractéristiques et leurs lacunes ainsi qu’en identifiant les angles morts dans la couverture des dimensions inégalitaires persistantes au sein des secteurs clés du DIG (milieux économiques, systèmes éducatifs, domaine de l’enseignement supérieur et de la recherche ), nous cernons des enjeux qui sont au cœur de la mission de l’Observatoire.
Keywords: 2000 à aujourd'hui; OFDIG; afrique; amériques; approches et analyses; discipline; développement durable; empowerment; féminisme décolonial; genre; identités LGBTQIA2+; inégalités; point de vue situé; périodes historiques; ressource en ligne; régions géographiques; statistiques; systèmes d'oppressions; thématiques

Systems thinking in COVID-19 recovery is urgently needed to deliver sustainable development for women and girls - Omukuti, Jessica; Barlow, Matt; Giraudo, Maria Eugenia; Lines, Tallulah; Grugel, Jean (The Lancet Planetary Health, 2021)
In low-income and middle-income countries, such as those in sub-Saharan Africa and Latin America, the COVID-19 pandemic has had substantial implications for women’s wellbeing. Policy responses to the COVID-19 pandemic have highlighted the gendered aspect of pandemics; however, addressing the gendered implications of the COVID-19 pandemic comprehensively and effectively requires a planetary health perspective that embraces systems thinking to inequalities. This Viewpoint is based on collective reflections from research done by the authors on COVID-19 responses by international and regional organisations, and national governments, in Latin America and sub-Saharan Africa between June, 2020, and June, 2021. A range of international and regional actors have made important policy recommendations to address the gendered implications of the COVID-19 pandemic on women’s health and wellbeing since the start of the pandemic. However, national-level policy responses to the COVID-19 pandemic have been partial and inconsistent with regards to gender in both sub-Saharan Africa and Latin America, largely failing to recognise the multiple drivers of gendered health inequalities. This Viewpoint proposes that addressing the effects of the COVID-19 pandemic on women in low-income and middle-income countries should adopt a systems thinking approach and be informed by the question of who is affected as opposed to who is infected. In adopting the systems thinking approach, responses will be more able to recognise and address the direct gendered effects of the pandemic and those that emerge indirectly through a combination of long-standing structural inequalities and gendered responses to the pandemic.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; afrique; afrique subsaharienne; amérique latine; amériques; approches et analyses; environnement; justice climatique; justice sociale; pandémie; patriarcat; politiques publiques; projet charge mentale; périodes historiques; racisme; régions géographiques; santé; santé publique; sexisme; systèmes d'oppressions; thématiques

Challenging gender equality in South African transformation policies - a case of the White Paper: A programme for the transformation of higher education - Akala, Betty M. (South African Journal of Higher Education, 2018)
Using a post-structural lens, I make arguments against homogenising people’s conditions and circumstances. In particular, I acknowledge that the post-1994 reform agenda intended to streamline the previously fragmented and segregated higher education landscape under the apartheid regime. Black women, who are the main target of this article suffered triple marginalisation ‒ race, social class and sexism. The aim of the article is to show the tensions that exist within the White Paper: A Programme for the Transformation of Higher Education (DoE 1997). The said tensions have stifled the attainment of gender equity and equality; effectively widening the gender fissures in post-1994 South African higher education. I argue that we should not take for granted phrases such as “equal opportunities” and “equal access” in policies. Instead, we should seek their meaning and achievement inter alia in earnest for the targeted group.Therefore, I postulate that gender and gendering is complex and very fragmented. For this reason, formulating transformation interventions on the premise of equality for all does not necessarily guarantee gender equality or gender equity. With this in mind, a “one-size fits all” approach to redressing gender equality is implausible and does not suffice in addressing salient gender injustices. I propose a multifaceted approach, which encompasses a realistic and holistic outlookon the divergent needs of black women in particular and women in general as a possible solution to the current challenges.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; afrique; afrique du sud; approches et analyses; discipline; histoire et politique; patriarcat; post-structuralisme; projet charge mentale; périodes historiques; racisme; ressource en ligne; régions géographiques; science de l'éducation; sexisme; système colonial; systèmes d'oppressions; thématiques; travail; éducation des femmes*

Living a feminist life - Ahmed, Sara (Duke University Press, 2017)
In Living a Feminist Life Sara Ahmed shows how feminist theory is generated from everyday life and the ordinary experiences of being a feminist at home and at work. Building on legacies of feminist of color scholarship in particular, Ahmed offers a poetic and personal meditation on how feminists become estranged from worlds they critique-often by naming and calling attention to problems-and how feminists learn about worlds from their efforts to transform them. Ahmed also provides her most sustained commentary on the figure of the feminist killjoy introduced in her earlier work while showing how feminists create inventive solutions-such as forming support systems-to survive the shattering experiences of facing the walls of racism and sexism. The killjoy survival kit and killjoy manifesto, with which the book concludes, supply practical tools for how to live a feminist life, thereby strengthening the ties between the inventive creation of feminist theory and living a life that sustains it. https://www.saranahmed.com/
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; afro-féminisme; approches et analyses; care; corps; cours; discipline; fem1000; féminismes noirs; incontournable; intersectionnalité; manifeste; militance; occident; orient; philosophie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; émotions; études culturelles

Rapport sur le développement humain en Afrique 2016 : accélérer les progrès en faveur de l'égalité des genres et de l'autonomisation des femmes en Afrique (PNUD, 2016)
Les disparités entre les genres coûtent quelque 95 milliards de dollars US par an en moyenne à l’Afrique subsaharienne et ont culminé à 105 milliards de dollars de pertes en 2014 (soit 6 % du PIB régional), compromettant de ce fait les efforts du continent en faveur d’un développement humain et d’une croissance économique inclusifs, indique le Rapport. Le rapport du PNUD analyse les facteurs politiques, économiques et sociaux qui entravent la promotion de la femme en Afrique et propose des politiques et des mesures concrètes pour combler l’écart entre les genres. Il s’agit notamment de corriger la contradiction entre la législation et la pratique afin de passer d’une égalité des genres juridique à une égalité de fait, de rompre avec les normes sociales préjudiciables aux femmes et de transformer les cadres institutionnels discriminatoires, en vue de garantir la participation économique, sociale et politique des femmes. D’après le rapport, une augmentation de 1 % de l’indice d’inégalité de genre contribuerait à réduire l’indice de développement humain (IDH) d’un pays de 0,75 % [...]
Keywords: 2000 à aujourd'hui; 2010-2019; EDI; afrique; approches et analyses; autonomisation; discipline; inégalités; pauvreté; périodes historiques; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; égalité des sexes; épistémologie

Travail-famille : un défi pour les femmes à Cotonou - Adjamagbo, Agnès; Gastineau, Bénédicte; Kpadonou, Norbert (Recherches Feministes, 2016)
En Afrique de l’Ouest, le taux d’activité des femmes est élevé. Souvent cantonnées dans le secteur informel, elles contribuent pourtant de façon  importante aux revenus du ménage. Toutefois, les rôles socialement prescrits imposent aux femmes la quasi-intégralité des tâches domestiques et des soins aux enfants. Cet article étudie la manière dont  les femmes actives à Cotonou, au Bénin, gèrent leur quotidien entre contraintes familiales et obligations professionnelles. L’analyse montre  que la conciliation incombe à toutes les femmes, quel que soit leur milieu socioéconomique. La différence se joue plutôt dans les ressources sociales et financières dont elles disposent pour pallier le fardeau de  la double journée.
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; approches et analyses; bénin; charge mentale; conciliation famille-travail; discipline; division sexuelle du travail; double journée de travail; démographie; famille; inégalités; maternité; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; stéréotypes de genre; systèmes d'oppressions; thématiques; travail; travail domestique

A gendered human rights analysis of Ebola and Zika: Locating gender in global health emergencies - Davies, Sara E.; Bennett, Belinda (International Affairs, 2016)
Globally gender remains a key factor in differing health outcomes for men and women. This article analyses the particular relevance of gender for debates about global health and the role for international human rights law in supporting improved health outcomes during public health emergencies. Looking specifically at the recent Ebola and Zika outbreaks, what we find particularly troubling in both cases is the paucity of engagement with human rights language and the diverse backgrounds of women in these locations of crisis, when women-specific advice was being issued. We find the lessons that should have been learnt from the Ebola experience have not been applied in the Zika outbreak and there remains a disconnect between the international public health advice being issued and the experience of pervasive structural gender inequalities among those experiencing the crises. In both cases we find that responses at the outbreak of the crisis presume that women have economic, social or regulatory options to exercise the autonomy contained in international advice. The problem in the case of both Ebola and Zika has been that leaving structural gender inequalities out of the crisis response has further compounded those inequalities. The article argues for a contextual human rights analysis that takes into account gender as a social and economic determinant of health.
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; amérique latine; amériques; approches et analyses; care; droits des femmes*; inégalités; périodes historiques; ressource en ligne; régions géographiques; santé; santé publique; systèmes d'oppressions; thématiques

Identifications homosexuelles, construction identitaire et tensions postcoloniales entre le Cameroun et la France - Awondo, Patrick (L’Espace Politique, 2011)
L’article problématise la circulation de l’« identité homosexuelle » dans l’entre-deux de l’Occident et de l’Afrique. À partir de l’exemple camerounais, il montre comment des « tensions postcoloniales » parasitent le débat autour de l’homosexualité en se cristallisant notamment sur l’affrontement symbolique entre ordres moraux opposés. Au-delà des identifications sexuelles, l’analyse aborde aussi la situation des individus qui tentent par la migration d’échapper au régime de contrainte camerounais et se retrouvent dans la posture de « réfugié (homo)sexuel » en France, sans que pour autant la question de leur « identité » sexuelle soit « résolue ».
Keywords: 1900-1999; 1970-1979; 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; afrique; approches et analyses; cameroun; cours; discipline; europe; france; féminisme décolonial; hétérosexisme; identités LGBTQIA2+; inégalités; justice sociale; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

Honor killings in the Middle East and North Africa: a systematic review of the literature - Kulczycki, Andrzej; Windle, Sarah (Violence against women, 2011)
A systematic review of the research literature on honor killings in the Middle East and North Africa (MENA) indicates a paucity of studies relative to the presumed magnitude of the problem. Forty articles were reviewed and critically appraised, of which only 9 contained primary data and 11 presented original secondary analyses. Despite a recent increase in published studies, persistent methodological limitations restrict the generalizability of findings. Most studies focus on legal aspects, determinants, and characteristics of victims and perpetrators. Victims are mostly young females murdered by their male kin. Unambiguous evidence of a decline in tolerance of honor killings remains elusive.
Keywords: 2000 à aujourd'hui; 2000-2009; afrique; approches et analyses; cours; droits des femmes*; féminisme islamique; maghreb; moyen-orient; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sex2283; sexisme; systèmes d'oppressions; thématiques; violences

Femmes, travail et pratiques éducatives au Togo - Alabi, Féhint'owa Ami (Université du Québec à Montréal, 2010)
L'étude porte sur la question de la scolarisation des femmes et de l'éducation scolaire des filles et sur certains aspects socioculturels relevant des pratiques sociales qui entraveraient profondément la réussite scolaire des filles et excluraient les femmes du système éducatif formel. Sur le plan méthodologique, trois techniques d'investigation ont été utilisées: une étude documentaire, un questionnaire et des guides d'entrevues ont été soumis aux femmes et à des personnes ressources. Les résultats obtenus révèlent ce qui suit: 1. La division sociale du travail entre les hommes et les femmes, qui attribue aux femmes les travaux domestiques, les soins aux enfants, les élever, initier les filles aux valeurs traditionnelles, etc. n'est établie que sur les principes de la nature et de l'apparence physique de celles-ci. Étant donné qu'initialement, les femmes sont considérées comme le sexe ayant les aptitudes à pouvoir assumer facilement ces types de responsabilités. 2. Le système de la dot et les procédures du mariage selon le milieu, qui ont pour fondement la politique du système patriarcal, apparaissent comme une dette, un crédit à rembourser par le biais des divers services que les femmes rendent à leur mari et aux familles. En tel cas, pour s'accommoder aux normes sociales, pour se faire apprécier, les femmes adoptent certains comportements qui souvent les empêchent de jouir pleinement de leurs droits. 3. Le complexe d'infériorité par rapport aux hommes que les femmes intériorisent et transmettent aux filles, favorise généralement l'adoption d'une attitude de soumission totale, sinon d'esclavage, par celles-ci à l'égard de leur mari et des hommes en général. Ainsi, par peur d'être mal vu par la société, d'être jugées par leurs pairs, les femmes en viennent à accepter sans condition leur situation de dominées, d'exploitées et d'exclues du système scolaire. Pour y remédier, nous avons proposé des stratégies d'action axées sur la sensibilisation auprès des femmes par rapport à leurs droits fondamentaux, l'éducation des enfants sur une base équitable et l'application de programmes d'actions à l'endroit des différents acteurs et de la population. La prise en compte et la réalisation de ces approches de solution pourraient contribuer à améliorer les conditions pénibles de la surcharge du travail des femmes, à remédier aux conditions scolaires difficiles des filles, favorisant ainsi leur maintien aux études de même que leur réussite. ______________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : Patriarcat, Division sexuelle du travail, Rapports sociaux de sexes, Domination, Genre.
Keywords: 2000 à aujourd'hui; 2000-2009; IREF; afrique; afro-féminisme; approches et analyses; discipline; division sexuelle du travail; domination masculine; féminismes noirs; mémoires/thèses; patriarcat; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; togo; travail; travail des femmes*; éducation; éducation des femmes*

Lost boys, invisible girls: stories of Sudanese marriages across borders - Grabska, Katarzyna (Gender, Place & Culture, 2010)
Forced migration challenges and changes gender relations. The transnational activities of refugees resettled in the West create gender asymmetries among those who stay behind. This article explores the transnational marriages of young southern Sudanese women (‘invisible girls’), who either stayed in Sudan or remained in refugee camps in Kenya, to Sudanese men who were resettled to America, Canada or Australia (‘lost boys’). Incorporating gender as a relational category into the analysis of transnational practices that migrants and refugees engage in is important. The article argues that there is a need to put feminist analysis at the centre of transnational processes resulting from (forced) migration. It looks at the connections between different geographical locations, the impacts of the migration of young refugee men on bridewealth and marriage negotiations and the gender consequences for young women, men and their families. It is argued that transnational activities, such as marriage, contest, reconfigure and reinforce the culturally inscribed gender norms and practices in and across places. Transnational marriage results in ambiguous benefits for women (and men) in accessing greater freedoms. Anthropological analyses of marriage need a geographical focus on the transnational fields in which they occur. The article seeks to deepen understanding of the nuanced gendered consequences of transnationalism. It shows how gender analysis of actions taken across different locations can contribute to the theorisation of transnational studies of refugees and migrants.
Keywords: 2000 à aujourd'hui; 2000-2009; afrique; amériques; anthropologie; anthropologie sociale; approches et analyses; australie; canada; cours; discipline; histoire et politique; kenya; mariage; migration; océanie; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sex2283; sexisme; soudan; systèmes d'oppressions; thématiques; transnationalisme; états-unis

La sexualité entre sexisme et racisme: les descendantes de migrant·e·s du Maghreb et la virginité - Hamel, Christelle (Nouvelles Questions Féministes, 2006)
L'article présente le résultat d'une recherche sur la vie affective et sexuelle des jeunes Français-es descendant de migrant-e-s originaires du Maghreb, qui décrit comment les jeunes femmes se positionnent par rapport au principe de virginité. Alors que cette norme est un mode de contrôle de la sexualité des femmes, certaines le revendiquent, tandis que celles qui l'ont transgressé expriment combien cette décision leur fut difficile. Pour comprendre la prégnance de leur attachement à la valeur de la virginité, l'autrice replace leurs discours et pratiques dans le contexte social qui les a fait naître. Elle décrit donc comment les discriminations et la stigmatisation racistes façonnent l'expérience de vie de ces jeunes femmes et montre combien cette expérience du racisme se combine à l'expérience du sexisme dans les familles et dans la société globale. Ici, l'imbrication du sexisme et du racisme fait peser sur elles un système de contraintes complexe qui les soumet à des injonctions paradoxales. Ce n'est qu'au regard de ces injonctions que la revendication par certaines de cette norme qui par ailleurs les opprime devient intelligible.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; afrique; approches et analyses; corps; cours; discipline; europe; france; histoire et politique; intersectionnalité; maghreb; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sex2283; sexisme; sexualité; sociologie; systèmes d'oppressions; thématiques; virginité; études démographiques

Femmes et immigrées: corvéables à merci - Puech, Isabelle (Travail, genre et sociétés, 2006)
Dans le secteur des services, des milliers de femmes connaissent des formes d’exploitation salariale diffuses, peu visibles, socialement tolérées. Cet article propose de mettre en lumière un mode de gestion de la main-d’œuvre non qualifiée qui, sous couvert de flexibilité et de compression maximale des coûts, utilise les femmes les plus vulnérables sur le marché du travail – en particulier les femmes immigrées – comme variable d’ajustement. À partir d’une enquête de terrain menée auprès d’une population de femmes de chambre, l’article s’attachera à mettre au jour une face cachée des emplois précaires. Des emplois souvent à durée indéterminée qui ne protègent pas des conditions de travail pénibles, des temps de travail à rallonge, des salaires au rabais et des pratiques patronales frauduleuses.
Keywords: 1900-1999; 1970-1979; 1990-1999; 2000 à aujourd'hui; 2000-2009; afrique; afrique subsaharienne; approches et analyses; capitalisme racial; corps; cours; discipline; europe; france; inégalités; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; régions géographiques; sciences humaines; sexisme; soc1061; sociologie; système colonial; systèmes d'oppressions; thématiques; travail

Égalité femmes-hommes en Afrique de l'Ouest (Secrétariat du Club du Sahel et de l'Afrique de l'Ouest)
En Afrique de l’Ouest, de grandes inégalités entre les sexes persistent. Les femmes et les filles sont défavorisées dans de nombreux domaines et n’ont pas les mêmes opportunités que leurs homologues masculins. Le Secrétariat du CSAO a compilé les documents relatifs aux politiques et stratégies en matière de genre pour faciliter l’accès aux politiques et cadres institutionnels existants et leur diffusion.
Keywords: 2000 à aujourd'hui; 2010-2019; OFDIG; afrique; approches et analyses; inégalités; politique; périodes historiques; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; travail; égalité des sexes; égalité femme*-homme